Effect of hydrogen peroxide on sugar transport in Schizosaccharomyces pombe. Absence of membrane lipid peroxidation - Janda, S; Gille, G; Sigler, K; Höfer, M (Folia microbiologica, 1993)
Stationary unaerated cells of S. pombe containing endogenous substrates but not energized by any exogenous ones take up 2-deoxy-D-glucose, 6-deoxy-D-glucose, D-xylose and D-arabinose actively over diffusion equilibrium. The active uptake is inhibited by 20-100 mmol/L H2O2 which causes an increase in KT but has no effect on Jmax. This "competitive inhibition" indicates that H2O2 affects directly the sugar binding sites of the transporters. The ATP-binding site of the plasma membrane H(+)-ATPase is also affected by 100 mmol/L H2O2; the KT decreases 7-fold, Jmax about 2.5-fold. These effects are not likely to be mediated by membrane lipid peroxidation which appears to be lacking in S. pombe, and this lack may be one of the reasons for the high resistance of this yeast to H2O2. Because of this S. pombe represents a suitable system for studying direct effects of oxidants on membrane proteins.
Keywords: Carbonyl Cyanide m-Chlorophenyl Hydrazone; Membrane Proteins; Xylose; Deoxyglucose; fungální proteiny; Carbohydrate Metabolism; Arabinose; arabinosa; Catalase; Oxygen Consumption; karbonylkyanid-m-chlorfenylhydrazon; membránové lipidy; peroxidace lipidů; antimycin A; Schizosaccharomyces; Proton-Translocating ATPases; xylosa; Lipid Peroxidation; metabolismus sacharidů; transportní proteiny; aktivní transport; Carrier Proteins; katalasa; Biological Transport, Active; protonové ATPasy; peroxid vodíku; spotřeba kyslíku; membránové proteiny; Membrane Lipids; Antimycin A; Hydrogen Peroxide; deoxyglukosa; Fungal Proteins